Traffic light food labelling in schools and beyond - Pettigrew, Simone; Pescud, Melanie; Donovan, Robert (Sage Publications, 2012)
Objective: The present study investigated stakeholders’ reactions to the introduction of a traffic light food classification system in primary and secondary school canteens. Design: Interviews and focus groups were conducted with stakeholders approximately 18 months after the introduction of the traffic light system, followed by telephone and web-based surveys. Setting: The context of the study was Western Australia, where a comprehensive healthy food policy was recently introduced in government schools. Method: Stakeholder groups included parents, principals, teachers, canteen managers, and representatives of parents and citizens committees. Results: Participants reported high levels of acceptance of the traffic light system and supported its extension to nutrition education programmes targeting children and parents. Conclusion: The results suggest that there is likely to be considerable support for an extension of the traffic light policy to the health curriculum in schools and into other food provision contexts.